In Vitro and In Vivo Evaluation of Oral Controlled Release Formulation of BCS Class I Drug Using Polymer Matrix System - Mosab Arafat; Muhammad Sarfraz; Mohammad F. Bostanudin; Anna Esmaeil; Aisha Salam; Salahdein AbuRuz (Pharmaceuticals, 2021)
Diltiazem hydrochloride is a calcium channel blocker, which belongs to the family of benzothiazepines. It is commonly used to treat hypertension and atrial fibrillation. Even though the drug has high solubility, its high permeability and rapid metabolism in the liver can limit the bioavailability and increase the dose frequencies for up to four times per day. This study focused on a polymer matrix system not only to control the drug release but also to prolong the duration of bioavailability. The polymer matrices were prepared using different ratios of poloxamer-188, hydroxypropyl methylcellulose, and stearyl alcohol. In vitro and in vivo assessments took place using 24 rabbits and the results were compared to commercially available product Tildiem® (60 mg tablet) as reference. Overall, the rate of drug release was sustained with the gradual increase of poloxamer-188 incorporated with hydroxypropyl methylcellulose and stearyl alcohol in the matrix system, achieving a maximum release period of 10 h. The oral bioavailability and pharmacokinetic parameters of diltiazem hydrochloride incorporated in polymer matrix system were similar to commercial reference Tildiem®. In conclusion, the combination of polymers can have a substantial effect on controlling and prolonging the drug release pattern. The outcomes showed that poloxamer-188 combined with hydroxypropyl methylcellulose and stearyl alcohol is a powerful matrix system for controlling release of diltiazem hydrochloride.